Vaccination of rhesus macaques with the live-attenuated HSV-1 vaccine VC2 stimulates the proliferation of mucosal T cells and germinal center responses resulting in sustained production of highly neutralizing antibodies. Issue 4 (23rd January 2017) - Stanfield, Brent A.; Pahar, Bapi; Chouljenko, Vladimir N.; Veazey, Ronald; Kousoulas, Konstantin G.
Abstract: We have shown that the live-attenuated HSV-1 VC2 vaccine strain with mutations in glycoprotein K (gK) and the membrane protein UL20 is unable to establish latency in vaccinated animals and produces a robust immune response capable of completely protecting mice against lethal vaginal HSV-1 or HSV-2 infections. To better understand the immune response generated by vaccination with VC2, we tested its ability to elicit immune responses in rhesus macaques. Vaccinated animals showed no signs of disease and developed increasing HSV-1 and HSV-2 reactive IgG1 after two booster vaccinations, while IgG subtypes IgG2 and IgG3 remained at low to undetectable levels. All vaccinated animals produced high levels of cross protective neutralizing antibodies. Flow cytometry analysis of cells isolated from draining lymph nodes showed that VC2 vaccination stimulated significant increases in plasmablast (CD27 high CD38 high ) and mature memory (CD21 − IgM − ) B cells. T cell analysis on cells isolated from draining lymph node biopsies demonstrated a statistically significant increase in proliferating (Ki67 + ) follicular T helper cells and regulatory CXCR5 + CD8 + cytotoxic T cells. Analysis of plasma isolated two weeks post vaccination showed significant increases in circulating CXCL13 indicating increased germinal center activity. Cells isolated from vaginal biopsy samples collected over the course of the study exhibited vaccination-dependent increases in proliferating (Ki67 + ) CD4 + and CD8 + T cell populations. These results suggest that intramuscular vaccination with the live-attenuated HSV-1 VC2 vaccine strain can stimulate robust IgG1 antibody responses that persist for >250 days post vaccination. In addition, vaccination lead to the maturation of B cells into plasmablast and mature memory B cells, the expansion of follicular T helper cells, and affects in the mucosal immune responses. These data suggest that the HSV VC2 vaccine induces potent immune responses that could help define correlates of protection towards developing an efficacious HSV-1/HSV-2 vaccine in humans.